Formulasi Pembuatan Sediaan Eyeshadow dari Ekstrak Bunga Kecombrang (Etlingera elatior Jack) - Barus, Bunga Rimta; Kaban, Vera Estefania (Jurnal FARMASIMED (JFM), 2019)
One type of cosmetic or decorative cosmetic preparation is eyeshadow which contains a color pigment applied to the eyelid. The purpose of this study was to find out that kecombrang flower extract can be used as eyelid coloring. From the study to make eyeshadow preparations using dyes extracted from kecombrang flowers, to determine the stability of the eyeshadow by using kecombrang flower extract in storage at room temperature, and to find out whether eyeshadow preparations using extracts from kecombrang flowers cause irritation when used. Eyeshadow preparations from kecombrang flower extract (Etlingera elatior Jack) were made in various concentrations of 15%, 17.5%, 20%, 22.5%, 25% and blank preparations (without using kecombrang flower extract). Physical quality inspection of the preparation includes: color dispersion test (homogeneity), cracking test, and stock stability test. And for other tests carried out polishing tests (homogeneity) and irritation tests. Eyeshadow from kecombrang flower extract also does not cause irritation and is stable in room temperature storage for 30 days. Preparation of kecombrang flower extract with several good concentrations was used as eyeshadow preparations, stable eyeshadow preparations in storage at room temperature within 30 days, and the formulation of eyeshadow preparations using kecombrang flower extract as eyelid coloring did not cause irritation.